2020
DOI: 10.1016/j.surfcoat.2019.125269
|View full text |Cite
|
Sign up to set email alerts
|

A single parameter approach to enhance the microstructural and mechanical properties of beta Ti-Nb alloy via open-air fiber laser nitriding

Abstract: A single parameter approach to enhance the microstructural and mechanical properties of beta Ti-Nb alloy via open-air fiber laser nitriding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…When the laser tracks significantly overlapped, they tended to "crush" with each other and thus produce "peaks" where the roughest regions can be recognized on the surfaces of DC80 and DC100. A detailed explanation to the structure of the fully-covered samples, namely DC40 to DC100 had been reported elsewhere (Chan et al, 2020).The findings indicated that minimum overlapping between the laser tracks would give desirable results to obtain the crack-free surface.…”
Section: Surface Roughness and Topography Before And After Laser Nitridingmentioning
confidence: 80%
See 4 more Smart Citations
“…When the laser tracks significantly overlapped, they tended to "crush" with each other and thus produce "peaks" where the roughest regions can be recognized on the surfaces of DC80 and DC100. A detailed explanation to the structure of the fully-covered samples, namely DC40 to DC100 had been reported elsewhere (Chan et al, 2020).The findings indicated that minimum overlapping between the laser tracks would give desirable results to obtain the crack-free surface.…”
Section: Surface Roughness and Topography Before And After Laser Nitridingmentioning
confidence: 80%
“…In this study, we have reproduced the formation of laser-nitride layer on beta TiNb surface by open-air laser-nitriding as in the previous study (Chan et al, 2020), but with an extended range of the duty cycles from 5% (modulated mode) to 100% (continuous wave, CW mode). More importantly, the present study focuses on the characterization of functional properties, in particular anti-wear and anti-bacterial properties of laser-nitrided TiNb surfaces.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations